Determining the closest distances from the coracoid base and tip to neurovascular structures in acute high-grade acromioclavicular joint injuries: a cadaveric study - Amornrat Chookliang; Prapakorn Klabklay; Wachiraphan Parinyakhup; Tanarat Boonriong; Korakot Maliwankul; Hafizz Sanitsakul; Trisak Kingchan; Chaiwat Chuaychoosakoon (BMC Musculoskeletal Disorders)
Abstract Background High-grade acromioclavicular (AC) joint injuries often require coracoclavicular (CC) stabilization, which increases the risk of neurovascular injury due to coracoid process proximity to vital structures. Previous intact AC joint measurements may have underestimated the surgical risks of high-grade injuries with altered anatomy. Therefore, this study investigated the distance from the coracoid base and tip to the adjacent neurovascular structures in simulated acute high-grade AC joint injuries. Methods Eight freshly frozen cadaveric specimens, consisting of four male and four female specimens, were subjected to simulated high-grade AC joint injuries via AC capsule and CC ligament transection and deltotrapezial fascia detachment. Closest distances from the coracoid base and tip to the lateral border of adjacent neurovascular structures were measured in the supine, beach chair, and lateral decubitus positions. Results The distance from the coracoid base to the neurovascular structures varied significantly depending on the body position. The supine position provided the greatest distance, reducing the risk of neurovascular injury compared to the beach chair and lateral decubitus positions (p = 0.030 and p < 0.001, respectively). In contrast, the lateral decubitus position had the shortest distance, highlighting an increased risk of neurovascular injury. Conclusions This study demonstrates that the supine position provides the safest approach for minimizing neurovascular injury risk during surgical stabilization of high-grade AC joint injuries. These findings contribute to clinical practice by emphasizing the importance of patient positioning to optimize surgical safety and outcomes. Clinical trial number Not applicable.